After the funeral of Ben Reitman. From left to right: Andrew Marfian, Jimmy Sheridan, Herby Shaw, Carl Schile, Laurenz Harris, Sam Byers. Text under the photo. From: The Chicago Daily News
After the funeral of Ben Reitman. From left to right: Andrew Marfian, Jimmy Sheridan, Herby Shaw, Carl Schile, Laurenz Harris, Sam Byers. Text under the photo. From: The Chicago Daily News.